Using ADDIE model to develop learning materials of the test of English proficiency in Edmodo - Fatma Rahayu Nita; Fitri Rahmawati Astiandani; Agnes Lintangsasi Wicaksono; Karunia Eka Nafilatul Janah (Universitas Merdeka Malang, 2022)
The preliminary analysis found that most of the students encountered several difficulties in achieving the target score of the Test of English Proficiency (TEP), such as low motivation and lack of vocabulary. Thus, this study attempts to develop the appropriate learning materials of the TEP preparation course for English Department students through Edmodo as the Learning Management System (LMS). Through the Research and Development method and employed the ADDIE model, 15 (fifteen) English Department students were involved as the research subject. Various procedures used in the ADDIE are: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The results show that the students perceived positive perception towards TEP learning materials, the content of the materials, and Edmodo as the LMS for the TEP preparation course. Finally, some suggestions are also given for further researchers: providing tutorials and creating a more colourful design. DOI: 10.26905/enjourme.v7i1.7036